Artificial Intelligence-based Energy Optimization : Applications in Internet of Things Communications - Mohammed ASSAOUY (Faculté des Sciences de Rabat, 2021)
Most common power source for connected objects still mainly battery-based. With limited power capacity, objects continually require local intervention to replace batteries when empty. Which can be difficult to achieve, especially when placed in hostile and dangerous environments.
Optimisation de l’Energie basée sur l’Intelligence Artificielle: Applications aux communications de l’Internet des Objets
Keywords: Sciences de l’ingénieur; Sciences de l’ingénieur